2022
DOI: 10.3389/fpubh.2022.861762
|View full text |Cite
|
Sign up to set email alerts
|

Female Firefighter Work-Related Injuries in the United States and Canada: An Overview of Survey Responses

Abstract: ObjectivesThis study explored how demographic characteristics, life experiences, and firefighting experiences have an impact on work-related injuries among female firefighters, and described events surrounding such work-related injuries.MethodsThis online survey was available from June 2019 to July 2020. Questions related to demographic characteristics, life experiences, firefighting experiences, and work-related injuries. Descriptive analyses characterized variables by the presence or absence of work-related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Polish and foreign literature list several works on the physical fitness of firefighters, and the influence of fitness on the effective implementation of rescue operations. Garano (23) showed that ballbased team sports played by firefighters while on duty bring financial consequences to the system in the form of prolonged indisposition of injured firefighters, the need for replacements, as well as injury compensation for injured officers. In some cases, an injury suffered during a ball game may be the reason for early retirement.…”
Section: Discussionmentioning
confidence: 99%
“…Polish and foreign literature list several works on the physical fitness of firefighters, and the influence of fitness on the effective implementation of rescue operations. Garano (23) showed that ballbased team sports played by firefighters while on duty bring financial consequences to the system in the form of prolonged indisposition of injured firefighters, the need for replacements, as well as injury compensation for injured officers. In some cases, an injury suffered during a ball game may be the reason for early retirement.…”
Section: Discussionmentioning
confidence: 99%
“…Approval to conduct this study was provided by the University of British Columbia Children’s and Women’s Research Ethics Board (H18-03318). The survey was advertised on industry-specific magazine sites and blogs and via postings and email lists by agencies as described by Pawer et al ( 22 ), and snowball sampling was employed ( 23 ). The purpose of the study was to describe work-related injury and cancer experiences among female firefighters.…”
Section: Methodsmentioning
confidence: 99%
“…Respondents were asked to provide information on their demographics, lifestyle (e.g., tobacco and alcohol use), firefighter career (e.g., department, rank), work-related injuries, and cancer and precancer diagnoses, as described by Pawer et al ( 22 ). Other lifestyle information considered in this study include hormone use, experience of full-term pregnancy and delivery and if the respondent had breastfed, and family history of cancer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The statistical analysis of the body parts injured for FFs is shown in Table 6. The evaluation of the data reported in the open literature was based on six of the fifteen independent studies, which identified and evaluated information related to body parts injured during firefighting activities [36,40,42,43,46,47]. Additionally, considering that the NFPA-published data on injuries was just discretized and reported since 2015, the data collected and analyzed in this study for the NFPA only considered the percentage of body parts injured from 2015 to 2019 [48].…”
Section: Analysis and Ranking Of Body Parts Injuredmentioning
confidence: 99%